Intervention for Burnout: A Review of Empirical Evidence - Kahill, Sophia (Canadian Journal of Counselling and Psychotherapy, 2011)
The literature in the field of professional burnout has grown enormously over the past decade. Burnout interventions have been discussed frequently, but with very little empirical justification. Even in the scholarly press, however, most publications have been non-empirical in nature. The current paper examines the existing empirical evidence on interventions for burnout in the helping professions, published from the introduction of the concept in 1974 to mid-1986.